2013
DOI: 10.1386/macp.9.1.27_1
|View full text |Cite
|
Sign up to set email alerts
|

Climate change communications & young people in the Kingdom: A reception study

Abstract: Based on focus groups with young people in England and Scotland and in-depth interviews with journalists, communication professionals and campaigners, this article examines how UK youths perceive climate change issues and how they receive climate messages from the news media and other communication forms. We found a strong sense of pessimism and disempowerment among our participants and identified a set of ‘triple-R reasons’ for their disengagement and inaction – namely the lack of relevance, resources and rit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 1 publication
(3 reference statements)
1
37
0
3
Order By: Relevance
“…These types of studies predominantly apply a quantitative approach through, for instance, a survey design where public attitude or knowledge levels are measured before and after a message exposure. A third grouping of articles concentrates on audience reception of communication messages, thus seeking insights into audience interpretations . These undertakings are often qualitative in nature and apply research methods such as in‐depth or focus group interviews.…”
Section: Results: Climate Change Communication—a Theoretical Perspectivementioning
confidence: 99%
“…These types of studies predominantly apply a quantitative approach through, for instance, a survey design where public attitude or knowledge levels are measured before and after a message exposure. A third grouping of articles concentrates on audience reception of communication messages, thus seeking insights into audience interpretations . These undertakings are often qualitative in nature and apply research methods such as in‐depth or focus group interviews.…”
Section: Results: Climate Change Communication—a Theoretical Perspectivementioning
confidence: 99%
“…The situation for young people is no different. Research from the UK and Australia indicates that concerns about the economy, employment opportunities and access to affordable education trump worries about issues like climate change for the people in 15–26 age range . The post‐2008 global economic downturn appears to have resulted in a re‐prioritization of economic concerns for many people; a particularly pronounced trend for young adults as they seek employment and to establish careers .…”
Section: Public Perceptions Of Climate Change: Are Young People Diffementioning
confidence: 99%
“…In an analysis of United States (US) media and political debate from the late 1990s and onwards, Nisbet and Scheufele (2009) (Boykoff, 2008), describing climate change as sensational, alarming (Hibberd and Nguyen, 2013;Russill and Nyssa, 2009), and harmful (Ambler, 2007;Carvalho and Burgess, 2005;Zamith et al, 2013). On the other hand, contradictory to the Pandora's box frame, the news media have also depicted climate change as a conflict over the uncertainties of anthropogenic climate change, starting from the assumption that climate scientists disagree about the human contribution to increases in GHG emissions (McIlwaine, 2013).…”
Section: Media Frames Of Climate Changementioning
confidence: 99%
“…For example, Hibberd and Nguyen (2013) argue that, due to a lack of positive and relevant messages, UK media messages have tended to hinder UK youths from becoming more actively involved. Similarly, Olausson (2011) found that emotional reporting, the commercial preconditions of the news media, and a lack of continuity and integration were likely to hamper rather than encourage Swedish public engagement in climate change responses.…”
Section: The Relationship Between Information On and Perception Of CLmentioning
confidence: 99%
See 1 more Smart Citation